Alexithymia and Inflammatory Bowel Disease: A Systematic Review - Martino, Gabriella; Caputo, Andrea; Schwarz, Peter; Bellone, Federica; Fries, Walter; Quattropani, M. C.; Vicario, C. M. (Frontiers in Psychology, 2020)
Background: Given the role of alexithymia - as the inability to identify, differentiate and express emotions - in chronic and immune-mediated illness, this systematic review analyzed the prevalence of alexithymia in patients with inflammatory bowel diseases (IBD), mainly represented by Crohn’s disease (CD) and ulcerative colitis (UC). Methods: PRISMA guidelines were followed throughout this systematic review of the literature published between 2015 and 2020 in indexed sources from PubMed, PsycInfo, Scopus and Web of Science databases. Search terms for eligible studies were: “Inflammatory bowel disease” AND “Alexithymia” [Titles, Abstract, Keywords]. Results: The initial search identified 34 indexed scientific publications. After screening we found that 5 publications met the established scientific inclusion criteria. Overall, the mean value of alexithymia ranged from 39 to 53.2 (TAS-20 score), thus mostly falling in the normal range indicating no alexithymia (≤ 51). Comparisons of alexithymia between patients with UC and CD highlighted that patients with CD showed externally-oriented thinking and difficulties identifying feelings to a greater extent. Regarding comparisons with other samples or pathologies, patients with IBD were more alexithymic than healthy controls and less alexithymic than patients with major depressive disorder, but no difference was found when compared with patients with irritable bowel syndrome (IBS). Then, regarding correlations with other variables, alexithymia was positively associated with anxiety and depression, as well as with psychopathological symptoms and somatic complains. Conclusion: This systematic review suggests that patients with IBD cannot in general be considered significantly alexithymic at a clinically relevant extent. However, their greater alexithymic levels compared to healthy participants and the associations found between such levels and other relevant psychological variables and somatic distress may suggest a reactivity hypothesis according to which living with IBD may progressively lead to impaired emotion recognition over time. Specifically, the relationship between IBD and IBS should be further explored, paying deeper attention to the clinical psychological functioning of CD because such IBD condition seems to pose more emotional challenges to patients.